Arabic Learning by Using Hybrid Learning Model in University - Akla, Akla (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
The Arabic language learning for university students in University is faced by various problems that impact the lack of language proficiency. Some problems faced by university students come from negative learning attitudes, low motivation, unhappy feelings toward the Arabic course that tends to be boring as well as a non-supportive language environment. The use of Hybrid Learning approach in Arabic language learning was done by strengthening students’ physical and mental state. This research aims to: (1) analyze the Arabic language learning by using Hybrid Learning Approach, (2) analyze lecturers' technology literacy level in deciding the success of the learning process (3) analyze the effectiveness of  Hybrid learning model on students' learning outcomes in Arabic language.This study applied the Mixed-Method Research to examine students' Arabic proficiency and learning process by using Hybrid Learning approach..The research respondents in this study are college students who take an Arabic language subject that consist of 80 students in each College. The data collection technique used in this research is a test, questionnaire, and interview. The use of Hybrid learning in Arabic language learning can improve students' positive attitude and learning motivation. Besides, this also can enhance students’ Arabic language skills. The significance of the research is to solve various problems of Arabic language learning faced by lecturers. The implementation of Hybrid learning can create an effective learning environment that can enhance Arabic language skills. This research result can be applied by Arabic language lecturers to handle various problems regarding attitude and learning motivation.